1982
DOI: 10.1007/bf01805874
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated prostaglandins in patients with primary breast cancer: Relationship to clinical parameters

Abstract: SummaryDetermination of the levels of prostaglandin E2 (PGE2) and PGF2~ were carried out using homogenized primary human breast tumors. Measurable levels of both prostaglandins were found in all but one tumor examined. In most samples, the absolute PGF2~ level was higher than that of PGE2. Higher PGE2 levels are more often seen in postmenopausal women than in pre-or perimenopausal patients, though among postmenopausal women, PGE2 levels do not correlate with age. Thus, the ratio of P G F : P G E is higher in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…This agrees with Fulton et al (1982) who obtained more PGE2 from tumours of post-menopausal women compared with those who were pre-or perimenopausal. However, Watson et al (1984) found similar yields of both PGE2 and PGF2,-Age Overall, the breast tumour total PG-LM correlates with age.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This agrees with Fulton et al (1982) who obtained more PGE2 from tumours of post-menopausal women compared with those who were pre-or perimenopausal. However, Watson et al (1984) found similar yields of both PGE2 and PGF2,-Age Overall, the breast tumour total PG-LM correlates with age.…”
Section: Resultssupporting
confidence: 91%
“…Tumour size Overall, the tumour size correlated inversely with PG-LM production, in agreement with Rolland et al (1980) who measured microsomal PGE2 formation from added arachidonic acid, with Fulton et al (1982) who measured endogenously formed PGE2, and with Vergote et al (1985) who found a similar tendency with PGF2a. In contrast, Karmali et al (1983) and Watson et al (1987) found no relationship between PGs and tumour size.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Since prostaglandins possess both osteolytic (Klein & Raisz, 1970) by Campbell et al (1981). Fulton et al (1982). Karmali et al (1983) and Watson and Chuah (1985).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that tumour prostaglandin levels are elevated in patients with a poor prognosis (Bennett et al, 1977). Conversely, it has also been suggested that increased prostaglandin levels are associated with favourable prognostic indices (Karmali et al, 1983;Fulton et al, 1982;and Campbell et al, 1982). A further study (Wilson et al, 1980) found no relationship between prostaglandin levels and established prognostic factors.…”
mentioning
confidence: 99%